Reframing the Subject : Postwar Instructional Film and Class-Conscious Literacies - Ritter, Kelly (Book collections on Project MUSE., 2015)
"Ritter offers an extensive theoretical analysis of the alliance of the value systems inherent in postwar mental hygiene films (class-based ideals, democracy, patriotism) with writing education--an alliance that continues today by way of the mass digital technologies used in teaching online. She further details the larger material and cultural forces at work in the production of these films behind the scenes and their effects on education trends"--